2015
DOI: 10.1140/epjc/s10052-015-3287-y
|View full text |Cite
|
Sign up to set email alerts
|

Cosmic strings in $$f\left( R,L_m\right) $$ f R , L m gravity

Abstract: We consider Kasner-type static, cylindrically symmetric interior string solutions in the f (R, L m ) theory of modified gravity. The physical properties of the string are described by an anisotropic energy-momentum tensor satisfying the condition T t t = T z z ; that is, the energy density of the string along the z-axis is equal to minus the string tension. As a first step in our study we obtain the gravitational field equations in the f (R, L m ) theory for a general static, cylindrically symmetric metric, an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 149 publications
(170 reference statements)
0
35
0
Order By: Relevance
“…Houndjo [53] reconstructed f (R, T ) gravity by taking f (R, T ) = f 1 (R) + f 2 (T ) and it was shown that f (R, T ) gravity allowed for a transition of matter from a dominated phase to an acceleration phase. Harko and Lake [54] investigated cylindrically symmetric interior string like solutions in f (R, L m ) theory of gravity. In a recent paper [55], we explored the exact solutions of a cylindrically symmetric spacetime in f (R, T ) gravity and recovered two solutions, which corresponded to an exterior metric of cosmic string and a non-null electromagnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…Houndjo [53] reconstructed f (R, T ) gravity by taking f (R, T ) = f 1 (R) + f 2 (T ) and it was shown that f (R, T ) gravity allowed for a transition of matter from a dominated phase to an acceleration phase. Harko and Lake [54] investigated cylindrically symmetric interior string like solutions in f (R, L m ) theory of gravity. In a recent paper [55], we explored the exact solutions of a cylindrically symmetric spacetime in f (R, T ) gravity and recovered two solutions, which corresponded to an exterior metric of cosmic string and a non-null electromagnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…It also becomes important when some types of the topological effects are needed suddenly by assigning an independent metric. In the context of modified theories of gravity, cosmic strings are investigated in f (R) gravity [58,60], teleparallel theories [61][62][63], brane worlds [64], Kaluza-Klein models [65], Lovelock Lagrangians [66], Gauss-Bonnet [67][68][69], Born-Infeld [70,71], bimetric theories [72], non-relativistic models of gravity [73], scalar-tensor theories [74][75][76][77][78][79], Brans-Dicke theory [80][81][82][83][84][85], dilation gravity [86,87], non-minimally coupled models of gravity [88], Mimetic gravity [89] and, recently, in the Bose-Einstein condensate strings [90]. However, the cosmic string is still unexplored in gravity's rainbow setting.…”
mentioning
confidence: 99%
“…Hence, in order to determine the asymptotic form of the metric, the solutions presented in this paper must be matched onto the exterior cylindrically symmetric vacuum metric. In the case of cylindrical symmetry, and by assuming that the exterior gravitational field is described by standard general relativity, this metric is the Kasner metric [49][50][51][52]61,62],…”
Section: Discussion and Final Remarksmentioning
confidence: 99%